2013
DOI: 10.1093/bjc/azt009
|View full text |Cite
|
Sign up to set email alerts
|

The Scammers Persuasive Techniques Model: Development of a Stage Model to Explain the Online Dating Romance Scam

Abstract: Permanent WRAP URL:http://wrap.warwick.ac.uk/88503 Copyright and reuse:The Warwick Research Archive Portal (WRAP) makes this work by researchers of the University of Warwick available open access under the following conditions. Copyright © and all moral rights to the version of the paper presented here belong to the individual author(s) and/or other copyright owners. To the extent reasonable and practicable the material made available in WRAP has been checked for eligibility before being made available.Copies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
132
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(148 citation statements)
references
References 20 publications
2
132
1
3
Order By: Relevance
“…In the ''Agency Theory: Overview'' Section, we mentioned three of these conditions: asymmetric information, goal incongruity, and contract design. As we saw in the ''Perpetrators as Agents'' and ''Adverse Selection Severity and Relative Opportunities to Carry Out 7 Studies include personality traits such as fantasy proneness (Langenderfer and Shimp 2001;Whitty 2013), interpersonal influence susceptibility (Ganzini et al 1990;Langenderfer and Shimp 2001;Naylor 2007), and social-status fulfilment (Fischer et al 2013;Holtfreter et al 2008;Ross and Smith 2011); cognitive impairment (Langenderfer and Shimp 2001;Pinsker et al 2011), and cognitive biases (Cialdini 2007;Fischer et al 2013;Gabaix and Laibson 2006;Kahneman and Tversky 1984). 8 Less-informed investors are exploited by better-informed managers when the latter are quick to release good news and slow to release (or actually conceal) bad news about a firm (Kane 2003).…”
Section: Contract Design Consumer Scams and The Principal-agent Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In the ''Agency Theory: Overview'' Section, we mentioned three of these conditions: asymmetric information, goal incongruity, and contract design. As we saw in the ''Perpetrators as Agents'' and ''Adverse Selection Severity and Relative Opportunities to Carry Out 7 Studies include personality traits such as fantasy proneness (Langenderfer and Shimp 2001;Whitty 2013), interpersonal influence susceptibility (Ganzini et al 1990;Langenderfer and Shimp 2001;Naylor 2007), and social-status fulfilment (Fischer et al 2013;Holtfreter et al 2008;Ross and Smith 2011); cognitive impairment (Langenderfer and Shimp 2001;Pinsker et al 2011), and cognitive biases (Cialdini 2007;Fischer et al 2013;Gabaix and Laibson 2006;Kahneman and Tversky 1984). 8 Less-informed investors are exploited by better-informed managers when the latter are quick to release good news and slow to release (or actually conceal) bad news about a firm (Kane 2003).…”
Section: Contract Design Consumer Scams and The Principal-agent Modelmentioning
confidence: 99%
“…Age, nationality, culture, psychological disposition, irrationality, and cognitive bias have been proposed as core individual-level explanations by psychologists, behavioural economists, and criminologists (Lea et al 2009;Mears et al 2014;Tippett 2014). Distinct scam contexts, such as dating scams (Whitty and Buchanan 2012;Whitty 2013), written communication scams (Carter 2015), email scams (Isacenkova et al 2014;Konte et al 2009), and online auction scams (Aleem and Antwi-Boasiako 2011;Ramesh et al 2014;Wall 2007), have also received attention, along with investigations into regional specifications-e.g. within the USA and Australia (Langton and Baum 2010;ABS 2012).…”
Section: Introductionmentioning
confidence: 99%
“…9 Classic marketing strategies such as the foot-in-the-door technique (asking for small amounts of money first and gradually increasing the requests as the person continues to comply) and the door-in-the-face technique (asking for large amounts of money and gradually decreasing the amount until the person is willing to comply) have also been found effective. 9 Frank Stanjano and Paul Wilson analyzed face-to-face cons and found that attackers use a limited number of techniques to manipulate their victims. 16 In addition to classic persuasive techniques, I would argue that it' equally important to focus on the role the Internet plays in persuading individuals to part with their money.…”
Section: Vulnerability and Persuasive Techniquesmentioning
confidence: 99%
“…9 Victims idealize the fake persona, believing they have found the perfect romantic partner. Given that much of the communication is asynchronous, criminals have time to develop the illusion of the ideal person, making it easier to trick victims into falling in love with them.…”
Section: Vulnerability and Persuasive Techniquesmentioning
confidence: 99%
“…Millions of people across the globe are targeted on a regular basis with a growing variety of scams. These range from phishing scams in spam e‐mail that seek to trick victims into revealing personal information, to fake lovers grooming unsuspecting victims through romance sites into giving money, ‘gifts’ and personal information (Whitty , forthcoming). The limited research on victimisation illustrates substantial victimisation.…”
mentioning
confidence: 99%